2013
DOI: 10.1111/2041-210x.12083
|View full text |Cite
|
Sign up to set email alerts
|

Solving the pitfalls of pitfall trapping: a two‐circle method for density estimation of ground‐dwelling arthropods

Abstract: Summary1. Pitfall traps are widely used for investigating ground-dwelling arthropods, but have been heavily criticized due to their species-, habitat-and attractant-specific trapping radius which produces unreliable estimation of species diversity and density. 2. We developed a two-circle method (TCM) for simultaneously estimating densities of ground-dwelling arthropods and the effective trapping radius. Multiple pairs of traps are located different distances apart, and the intersection of trapping areas can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…The passive sampling of ground arthropods with pitfall traps, that is, small containers buried to the ground, was used in many biodiversity and conservation studies across the recent decades and is still being used today (Greenslade , Zhao et al. , Brown and Matthews ). The benefits of pitfall trap sampling are its time efficiency and the high probability to detect rare and nocturnal species that other methods might miss (Spence and Niemelä , Lang , Cardoso et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The passive sampling of ground arthropods with pitfall traps, that is, small containers buried to the ground, was used in many biodiversity and conservation studies across the recent decades and is still being used today (Greenslade , Zhao et al. , Brown and Matthews ). The benefits of pitfall trap sampling are its time efficiency and the high probability to detect rare and nocturnal species that other methods might miss (Spence and Niemelä , Lang , Cardoso et al.…”
Section: Introductionmentioning
confidence: 99%
“…The number of pitfall traps and their spatial arrangement have been shown to strongly influence the reliability of sampled densities for estimations of real densities (Scheller , Parmenter and MacMahon , Perner , Zhao et al. ). Moreover, only limited knowledge exists about how the species‐specific sampling bias may impact community‐level metrics considering variation in community structure across ecosystems, such as the distribution of species body masses across the abundance ranks (Topping and Sunderland ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…however, monoculture leads to landscape simplification and can cause decreasing of predatory arthropod population. According to Zhao et al (2013) ground-dwelling arthropods have significant functions in an agroecosystem, such as pest control and food chain maintenance. Nicholls et al (2008) reported that there are many ways in which enhanced plant biodiversity can contribute to the design of pest-stable agroecosystem.…”
Section: Introductionmentioning
confidence: 99%